Frontier governmentality - Muhammad Adeel Malik; Rinchan Ali Mirza; Faiz Ur Rehman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We examine whether frontier rule, which disallows frontier residents from recourse to formal institutions of conflict management and disproportionately empowers tribal elites, provides a more fragile basis for maintaining social order in the face of shocks. Combining a historical border that separates frontier from non-frontier regions in north-western Pakistan with 10km-by10km grid cell-level data on conflict in a spatial regression discontinuity design framework, we show that areas under frontier rule experienced significantly higher violence against the state after 9/11. We argue that the 9/11 tragedy represented a universal shock to grievances against the state which, in the absence of formal avenues of conflict management, led to a sharp surge in attacks against state targets in the frontier regions. We show that the surge in 'sovereignty-contesting' forms of violence in these regions was partly carried out through the systematic assassination of tribal elites upon whom the whole edifice of social order was built.
Keywords: D02; D74; N45; P48; 330; institutions; historical frontiers; conflict